2017
DOI: 10.1101/209742
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A toolbox of anti-mouse and rabbit IgG secondary nanobodies

Abstract: Polyclonal anti-IgG secondary antibodies are essential tools for many molecular biology techniques and diagnostic tests. Their animal-based production is, however, a major ethical problem. Here, we introduce a sustainable alternative, namely nanobodies against all mouse IgG subclasses and rabbit IgG. They can be produced at large scale in E. coli and could thus make secondary antibody-production in animals obsolete. Their recombinant nature allows fusion with affinity tags or reporter enzymes as well as effici… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…A similar gain in precision was observed previously using dSTORM. 12 Additionally, we performed an autocorrelation analysis on single microtubules to corroborate their difference in size, and we observed a significantly faster loss in autocorrelation for microtubules stained with 2.Nb (Fig. 2H).…”
Section: Secondary Nanobodies Provide Higher Staining Accuracy Than Smentioning
confidence: 67%
See 4 more Smart Citations
“…A similar gain in precision was observed previously using dSTORM. 12 Additionally, we performed an autocorrelation analysis on single microtubules to corroborate their difference in size, and we observed a significantly faster loss in autocorrelation for microtubules stained with 2.Nb (Fig. 2H).…”
Section: Secondary Nanobodies Provide Higher Staining Accuracy Than Smentioning
confidence: 67%
“…Although it has been already demonstrated that small primary affinity probes are able to minimize the linkage error, 4,8,12 there was just one indication performed in dSTORM that secondary nanobodies can increase the labelling precision. 12 Here we show, in addition to the resolution improvement by using 2.Nbs on DNA-PAINT and STED microscopy, that bulky secondary antibodies not accurately represent the distribution of the primaries, due to a combination of their polyclonal nature and large size (Fig. 1A).…”
Section: Smaller Size Of the Secondary Probe Decreases Linkage Error mentioning
confidence: 99%
See 3 more Smart Citations